2018
DOI: 10.1101/482745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enrichment of short mutant cell-free DNA fragments enhanced detection of pancreatic cancer

Abstract: 30Analysis of cell-free DNA (cfDNA) is promising for broad applications in clinical 31 settings, but with significant bias towards late-stage cancers. Although recent studies have 32 discussed the diverse and degraded nature of cfDNA molecules, little is known about its 33 impact on the practice of cfDNA analysis. Here we reported a new targeted sequencing by 34 combining single-strand library preparation and target capture (SLHC-seq). By applying 35 the new technology in plasma cfDNA from pancreatic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…This is consistent with a recent report that pancreatic cancer is among the low ctDNA cancers [41]. Emerging evidence indicated that tumor-derived cfDNA were shorter than those from nonmalignant cells, and enrichment of short fragments could improve detection of ctDNA [41,42]. Indeed, we also found that estimated TFx for samples with selection of short reads after sequencing was significantly higher than that of original samples (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent report that pancreatic cancer is among the low ctDNA cancers [41]. Emerging evidence indicated that tumor-derived cfDNA were shorter than those from nonmalignant cells, and enrichment of short fragments could improve detection of ctDNA [41,42]. Indeed, we also found that estimated TFx for samples with selection of short reads after sequencing was significantly higher than that of original samples (data not shown).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, using this approach, ctDNA could be detected in 88% of stage I/II pancreatic adenocarcinoma cases and in 95% of those with stage III/IV disease [41]. The analysis of cfDNA fragment size revealed that the DNA fragments that contained the wild-type KRAS allele were all around 160 bp in size, while a large proportion of the DNA fragments containing the mutant KRAs allele had size below 100 bp [41]. Interestingly, the short DNA fragments were more pronounced in the pre-cancerous stage and in early-stage pancreatic cancers [38].…”
Section: Ctdna In Pancreatic Cancermentioning
confidence: 99%
“…Liu and coworkers reported developing a single-strand library preparation and hybrid-capturebased ctDNA sequencing (SLHS-seq) approach. The procedure was applied to perform cfDNA profiling in a group of 112 pancreatic cancer patients, and the results demonstrated high specificity and sensitivity in the detection of ctDNA in pancreatic cancer patients, including those at an early stage of disease [41]. Indeed, using this approach, ctDNA could be detected in 88% of stage I/II pancreatic adenocarcinoma cases and in 95% of those with stage III/IV disease [41].…”
Section: Ctdna In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The current article describes a single-strand library preparation assay for the sequencing of cell-free DNA (cfDNA) in a clinical cohort of patients with PC or relevant pancreatic lesions and healthy controls [3]. A major pitfall of the cfDNA analysis is the contamination with high molecular weight genomic DNA, which originates from healthy blood cells when the blood is extracted and centrifuged for the retrieval of plasma.…”
mentioning
confidence: 99%